The Relationship between Intra-School Student Organization and Entrepreneurial Character Building of Students - Herawati, Herawati; Devilla, Rego; Rahmawati, Rahmawati; Elpisah, Elpisah (Indonesian Research Journal on Education, 2024)
This study aims to analyze the role of the Intra-School Student Organization (OSIS) in shaping the entrepreneurial character of students at SMAN 13 Pangkep. The method used is a qualitative approach with descriptive research design. Data collection was done through observation, interview, and documentation, focusing on the management and student council members. The results showed that student council activities help students in reading business opportunities, optimism, and future planning. OSIS serves as a forum for students to organize and channel creativity, although there are obstacles such as violations of daily responsibilities. The hope of student council administrators is that there will be entrepreneurship training to improve students' understanding. The findings are expected to influence education policy and encourage further research in this area.